EFEKTIVITAS PENERAPAN ASAS LANGSUNG, UMUM, BEBAS, RAHASIA, JUJUR, DAN ADIL DALAM PENYELENGGARAAN PEMILIHAN UMUM ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KOTA KUPANG TAHUN 2024 - Fallo, Markus; Ratu Udju, Hernimus; Lamataro, Cyrilius Wilton Taran (Petitum Law Journal, 2025)
This study examines the implementation of the principles of direct, general, free, secret, honest, and fair elections (LUBER JURDIL) in the 2024 elections for the Regional People's Representative Council (DPRD) of Kupang City. This research uses an empirical legal method with interviews as the primary data source conducted at the Election Commission (KPU), Election Supervisory Body (BAWASLU), and Kupang City Police Department. The findings indicate that the implementation of LUBER JURDIL in Kupang City has generally been effective, although several challenges such as lack of voter education, logistical delays, vote-buying, and voter data manipulation were encountered. Additionally, low voter participation hinders efforts to achieve fair and democratic elections. This study proposes increasing voter education and outreach, strengthening the integrity of election organizers, and fostering collaboration among relevant institutions to ensure a more transparent, accountable, and credible election process.